CURRENT STATE OF FORMATION OF LOCAL BUDGET REVENUES (Academia Science Repository, 2023)
All of us are witnessing that economic reforms along with reforms in all spheres in the Republic of Uzbekistan are showing their results on a large scale. As an example, it can be said that today, a number of practical works have been carried out to ensure the openness and transparency of state finances, including the state budget and extra-budgetary funds, to ensure the efficiency of financial flows in the budget system, to ensure the participation of the population in the distribution of budgets of the budget system. is increasing. State budget _ economic development of our country, structural changes aimed at increasing the competitiveness of Uzbekistan in the world market and strengthening its position in the implementation of long-term strategic goals, ensuring the production of competitive products based on modern high technologies, as one of the main financial sources for the rapid development of production attention is paid.